2016
DOI: 10.1016/j.electstud.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Coping with lengthy ballots

Abstract: Given voters' limited cognitive abilities, the learning environments voters face may have implications for how voters learn and make decisions. One prominent feature of American elections is the variation in the length of the ballot across jurisdictions and elections. This paper explores the consequences of lengthy ballots on the ability of voters to learn about candidates.Using an experimental design and a dynamic information board (Lau and Redlawsk, 2006), subjects participate in a mock election where they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with the results of studies of SMD elections that feature long ballots in some low-profile elections (Grant, 2017) or in California referendums (Bowler et al, 1992). With many candidates on ballots, voters spend significantly less time learning about individual candidates (Seib, 2016) and are more likely to vote for status quo or first-position candidates (Augenblick & Nicholson, 2016). Brockington (2003) links larger first-position bonuses to voters' being more poorly informed about candidates.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are consistent with the results of studies of SMD elections that feature long ballots in some low-profile elections (Grant, 2017) or in California referendums (Bowler et al, 1992). With many candidates on ballots, voters spend significantly less time learning about individual candidates (Seib, 2016) and are more likely to vote for status quo or first-position candidates (Augenblick & Nicholson, 2016). Brockington (2003) links larger first-position bonuses to voters' being more poorly informed about candidates.…”
Section: Discussionsupporting
confidence: 85%
“…The lower we read, the more tired we become and the less we are able to pay attention to what we see (see, e.g., Kim et al, 2015)—in our case information that signals similarity with the voter. Many authors have observed attention effect impacts when it comes to electoral ballots (for instance Augenblick & Nicholson, 2016; Coufalová & Mikula, 2023; Lutz, 2010; Miller & Krosnick, 1998; Seib, 2016).…”
Section: Results and Heterogeneity Analysismentioning
confidence: 99%
“…Yet the number of options on the ballot may be an important factor in either case (cf. Seib, 2016). Since the term "candidate supply" might suggest the mistaken assumption that the variable under consideration here is only relevant to candidate-centric electoral systems (such as the USA's), we use "ballot options" instead.…”
Section: Ballot Optionsmentioning
confidence: 99%